Teacher practices that promote productive dialogue and learning in mathematics classrooms. (2019) - Webb, Noreen M.; Franke, Megan L.; Ing, Marsha; Turrou, Angela C.; Johnson, Nicholas C.; Zimmerman, Joy
Highlights: Closely examining the mathematical details of classroom interaction is essential. Engaging in details of others' mathematical ideas relates to achievement. Productive teacher support depends on following up on invitations to students. Interaction varies across classroom participation structures. Abstract: This paper traces the development of a program of work that seeks to understand the teacher practices that promote productive dialogue and learning in mathematics classrooms. This work originated in cooperative/collaborative learning research, with a focus on understanding group dynamics effective for student learning. Over time, it layered on increasing attention to the teacher's role, and branched out to consider the multiple participation structures in the classroom (whole-class discussion, small-group collaborative work, private student-student conversations). Each phase of this work brought in a heightened focus on the details of classroom interaction around mathematics—both in the thinking that students share and in the practices teachers use to support student participation—to better understand the development of students' mathematics learning.